(untitled) (Impetus, 2021)
Glycemia is the value of glucose levels present in the blood, whose normal concentration in pre-prandial whole blood is 70 to 105 mg / dl and post-prandial after one hour is <140 mg / dl. When these values ​​are low or high, they are detrimental to health (Roviria, 2002). Therefore, the body regulates this concentration rigorously, mainly through the hormones insulin and glucagon (Lehninger, 2005; Trudy and James, 2003)